Bacteria associated with planktonic diatoms from Lake Baikal - I. S. Mikhailov; Y. R. Zakharova; N. A. Volokitina; D. P. Petrova; Y. V. Likhoshway (Acta Biologica Sibirica, 2018)
Algal-bacterial associations were studied in unialgal xenic cultures of Synedra acus subsp. radians, Asterionella formosa and Fragillaria crotonensis planktonic diatoms from Lake Baikal, using epifluorescent and scanning electron microscopy. It was found that rod- and ovoid-shaped bacteria colonized cell walls of diatoms. Cloning and sequencing of fragments of 16S rRNA gene in diatom cultures revealed members of Gammaproteobacteria (Pseudomonas sp.), Betaproteobacteria (Janthinobacterium sp., Hydrogenophaga sp., Methylophilus sp.), Bacteroidetes (Flavobacterium sp., Pedobacter sp.), and Acinobacteria (Nocardioides sp.).